2016
DOI: 10.1111/febs.13668
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint blockade in lymphoid malignancies

Abstract: Malignant cells may subvert and escape endogenous host immune surveillance by up‐regulation of immune inhibitory signals known as immune checkpoints. These checkpoints are important therapeutic targets, and antibodies that block checkpoint signaling have shown remarkable efficacy in some solid tumors as well as in some refractory hematologic malignancies. In hematologic cancers, the mechanism of these checkpoints is complex, as the tumor and immune system are one and the same. In this review, we evaluate the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Examples of these advances include inhibitors of the PI3K/mTOR pathway; 14, 15, 16 Bruton’s tyrosine kinase inhibitors, 17 immunomodulatory agents that have multiple effects on normal and malignant cells 18, 19, 20 and immune checkpoint inhibitors. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Examples of these advances include inhibitors of the PI3K/mTOR pathway; 14, 15, 16 Bruton’s tyrosine kinase inhibitors, 17 immunomodulatory agents that have multiple effects on normal and malignant cells 18, 19, 20 and immune checkpoint inhibitors. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Examples of these advances include inhibitors of the PI3K/mTOR pathway; [14][15][16] Bruton's tyrosine kinase inhibitors, 17 immunomodulatory agents that have multiple effects on normal and malignant cells [18][19][20] and immune checkpoint inhibitors. 21 Targeting the DNA hypermethylation in lymphoma has to date been limited to inhibitors of the DNMT enzyme. Clozel et al 2 demonstrated in vitro that azacytidine could inhibit DNMT and sensitize lymphoma cells to standard chemotherapy agents.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cognate ligands can engage cytotoxic T-lymphocyte associated protein 4 (CTLA-4) or programmed-death 1 (PD-1) on the surface of T cells, leading to the downregulation of T-cell function. 84,85 The association between immune checkpoints and development of MTX-LPD remains to be elucidated.…”
Section: Lymphocytes and Mtx-lpd: Transition Of The Peripheral Lymphomentioning
confidence: 99%